Marketplaces Movements, Representations and Practices (Taylor & Francis, 2023)
"This edited volume portrays marketplaces from a mobility perspective as dynamic and open entities consisting of flows of people, goods and ideas. There is a renewed interest in research and policy arenas in marketplaces as the core of cities' spatial and economic development and sociocultural life, as incubators of urban renewal and platforms of alternative consumption models and as source of livelihood for many people worldwide. Contributions of this book draw on notions of movements, representations and practices to illustrate that markets have physical reality but are also culturally and socially encoded, and experienced through practice. It brings together empirically evidenced scholarly and practice-based works from the United Kingdom, the Netherlands, Switzerland, Spain, Bulgaria, Turkey, Lebanon, Peru, Brazil, Vietnam, South Africa and India. This book is primarily intended for scholars and graduate students of urban geography, urban design and planning, sociology, anthropology, who are interested in the relation between place and mobility in general, and markets as 'knots' in the city, in particular. It also informs policy-makers how urban planning policies and design interventions for marketplaces may foster more socially inclusive and environmentally just cities."
English
Keywords: Geography; Human geography; Geography, Social Sciences, Urban Studies, marketplaces, representational theory, urban mobility, everyday geographies